Integrasi Kosmologi Jawa dan Ekoteologi Islam dalam Pemikiran Seyyed Hossein Nasr - Rahmayani, Della; Ismi Nur Hidayah; Isnaini A sifa Rohmah; Syahru Fajar Ibrahim; Rohim Habibi (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2025)
This study examines the integration between the Javanese cosmology Hamemayu Hayuning Bawono and Islamic ecotheology in the thought of Seyyed Hossein Nasr. The synthesis of these two perspectives forms a comprehensive and contextual framework of Islamic eco-spirituality in the Indonesian context, which can be applied in daily life. Both Javanese philosophy and Nasr’s thought regard nature as a sacred creation of God, implying that humans bear a moral and spiritual responsibility to preserve it. The principle of Hamemayu Hayuning Bawono, which emphasizes the harmony and beauty of the world, aligns with Nasr’s cosmological concept of tawhid, which highlights the unity of God, humanity, and nature. Both perspectives stem from the awareness that today’s environmental crisis is essentially a spiritual crisis caused by the loss of the sacred perception of nature. This integration not only provides a theoretical contribution to the development of Islamic ecological discourse but also offers practical implications through the strengthening of environmental ethics in education, public policy, and religious social movements such as EcoMasjid and Green Pesantren. Eco-spiritual awareness rooted in spiritual values and local wisdom can reinforce an Indonesian ecological ethic grounded in Islamic teachings. However, since this study is literature-based, further interdisciplinary research involving theology, ecology, and anthropology is needed to deepen and evaluate the implementation of Islamic eco-spirituality concepts within society.